Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1590/s1809-98232010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da mortalidade em população idosa de municipios do Rio Grande do Sul no período de 1996 a 2004

Abstract: Estima-se que, no Brasil, a população com 60 anos ou mais será em torno de 34 milhões em 2025. O idoso vivencia em seu processo de envelhecimento uma série de alterações, que proporcionam o aparecimento de uma série de doenças que podem conduzi-lo ao óbito. Diante de tal realidade, o objetivo deste estudo foi analisar a evolução na taxa de mortalidade em idosos de municípios do interior do estado do Rio Grande do Sul, no período de 1996 a 2004, levando em consideração as faixas etárias e as diferenças entre os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
3
1
0
2
Order By: Relevance
“…Similar results were found in other Brazilian studies on mortality in the elderly caused by various diseases of the circulatory system [23][24][25][26] .…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were found in other Brazilian studies on mortality in the elderly caused by various diseases of the circulatory system [23][24][25][26] .…”
Section: Discussionsupporting
confidence: 91%
“…The study identified a higher proportion of deaths in long-lived old people, with a result similar to others performed in different regions of Brazil [14][15][16][17][18] . Similar to other studies, deaths were more frequent in men 14,16,19 .…”
Section: Discussionsupporting
confidence: 85%
“…The study identified a higher proportion of deaths in long-lived old people, with a result similar to others performed in different regions of Brazil [14][15][16][17][18] . Similar to other studies, deaths were more frequent in men 14,16,19 . One of the hypotheses is that women, generally attend health services 20,21 , perform more prevention practices such as reducing the consumption of salt and fatty diet, less alcohol and smoking 20 and culturally experience a greater practice of self-care when compared to men, and since their pre-adolescence they are encouraged to perform gynecological and preventive exams 22 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…6 No Brasil, estudos sobre idosos apontam que os maiores coeficientes de mortalidade relacionam-se a doenças do aparelho circulatório, do aparelho respiratório e neoplasias. [7][8] As doenças cardiovasculares foram responsáveis por 31% dos óbitos no Brasil, em 2002, destacando-se os óbitos por doenças cerebrovasculares (DCBV) e doenças isquêmicas do coração (DIC). Em alguns estados, como São Paulo e Rio Grande do Sul, as DIC ocupam o primeiro lugar como causa de mortalidade; já no Rio de Janeiro, as DCBV ultrapassam as DIC proporcionalmente, embora na Capital e noutras cidades do estado, as DIC ocupem o primeiro lugar entre as principais causas de óbito.…”
Section: Introductionunclassified